DEVELOPING LEARNING MATERIAL FOR TEACHING WRITING RECOUNT TEXT USING STAD TECHNIQUE FOR THE TENTH-GRADE STUDENT - Tama, Gerhard Wira; Regina, Regina; Ikhsanudin, Ikhsanudin (JOEEL (Journal of English Education and Literature), 2021)
This study was aimed to develop learning material for teaching writing recount text using STAD technique to the tenth-grade Students. The researcher developed the learning material because there were conditions in the class which do not support the situation in the learning process, The Learning process in writing skill, some students passive in the class so make the students not motivated and the learning process is not going well, and also the material used in the school is not complete enough. The procedure was based on ADDIE but because of the situation in this era (COVID-19), the research was conducted ADD ( Analyze, Design, and Develop). It was conducted through the following analyzing the needs, designing the framework, and Developing the material. The learning material for teaching writing recount text using STAD technique had been validated by the expert: the learning material is appropriate with some revisions. The researcher suggested that further development of learning material for teaching recount text using STAD, for the next developers who conduct the same product to make it more complete (ADDIE) until the Implementation and Evaluation section in the class to make the learning material better